Extensibility of External Magnetic Potential at High Latitudes - Antarctica - Kumar, C. P. Anil; Akhila, J. C. K.; Sherin A., Ann (My University, 2023)
We investigated the external magnetic potential due to solar forcing, with nine years of data during 2001-2009, covering the deep solar minimum (2006-2009), at two stations: one is in the polar cap -Vostok (78º27'S, 106º52’E; mag. lat 83ºS) and another is in the subauroral region - Maitri (70º45'S, 11º43'E: mag. lat 67ºS) in Antarctica. The significance of the work is associated with space weather prediction and its impact on planet Earth. We used Advance Composition Explorer (ACE) satellite data for the aforesaid period for a thorough understanding of influences due to solar wind origin and to compare the parameter observed in these regions. We used the spherical cap harmonic analysis (SCHA) function as a tool. The inference indicates that at Vostok the magnitude is enhanced throughout and depicts a broad ambient external magnetic potential. It seems to be essentially the intensification of the region 1 currents whereas at Maitri intense electric fields are produced during geomagnetic perturbations which drive a system of disturbed time Region 2 currents over the quiet time currents. During this scenario in Maitri there are noticeable peaks or enhancements in the magnetic potential that can be observed mainly during geomagnetic disturbances. Hence the regression relation developed for external magnetic potential calculation, in terms of solar wind parameters agrees well with polar cap region and the area is relatively less explored earlier, the present investigation can be expected to add knowledge about that regime.
Keywords: Antarctica; External magnetic potential; Electrodynamics; Global electric circuit; Spherical cap harmonic analysis